Long-term functional outcomes of sacrococcygeal teratoma – A systematic review of published studies exploring ‘real world’ outcomes - Salim A. (2023)
Sacrococcygeal teratoma (SCT) is a rare neoplasm affecting 1:35,000 newborns. Long-term follow-up from small observational studies report impaired bladder/bowel function. This current study comprehensively analyses all published studies to better define true long-term functional sequelae. Medline/Embase databases were searched with PRISMA guidelines. Final analysis yielded 37 studies involving 1116 patients (854 female; 77%). Individual datasets were available in 14 studies (222 patients). According to Altman classification - 298/845 (35%) were Type I, 252/845 (30%) Type II, 133/845 (16%) Type III, and 128/845 (15%) Type IV tumours. Most neoplasms were benign (640/858; 75%), 77/858 (9%) immature and 141/858 (16%) malignant. Abnormal bladder function was reported in 7/39 (18%) Altman Type I, 23/61 (37.7%) Type II, 11/34 (32.4%) Type III, and 15/25 (60%) Type IV cases (p = 0.007). Adverse urological outcomes were notably common in immature/malignant neoplasms vs benign tumours and in patients requiring reoperation(s); p = 0.002 and p = 0.01. Bowel dysfunction was evident in 19% index cases and constipation in 26% with no significant association(s) with tumour characteristics. Higher Altman stage, unfavourable tumour biology and reoperation are associated with poor functional outcome(s). Multidisciplinary management from primary diagnosis of SCT is crucially important for all patients to best optimise functional outcomes across surgical specialities.